GENRE-BASED INSTRUCTION (GBI): THE CONCEPT AND ITS APPLICATION TO FOREIGN LANGUAGE CLASSROOM - Rita Erlinda (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2008)
Since the implemetation of KBK and KTSP, the goals of teaching English at schools are emphasized on the mastery of four language competences-linguistic, strategic, sociolinguistic and actional-which will lead to the mastery of discourse competence. Those competences are realized in for language skills (listening, speaking, reading and writing) through the analysis of texts (genres). Therefore, one of the approaches to facilitate the accomplishment of the goals is Genre-based Instruction (GBI). This approach is mainly a language teaching program which is based upon Genre Analysis Technique. This technique deals with anaysing text, both spoken and written, in order to figure out social or commnicative functions, genre structures, lexico-grammatical features of particular genres. Consequently, the learners are able to use the language for appropriate situational and cultural contexts.Key Words: genre, genre analysis, genre-based instruction (GBI), foreign language classroom, functional grammar